Reapprendre à voir: (at)vaizdai, simptomai ir pasirodymo medija - Vachninas, Benediktas (Problemos, 2023)
Emmanuel Alloa interviewed by Benediktas Vachninas Emmanuel Alloa, Professor of Aesthetics and Philosophy of Art at the University of Fribourg, is one of the most active contemporary thinkers in the field of new visual studies. His areas of research include aesthetics, phenomenology, theories of image, theories of media, and the French philosophy. Professor Alloa has authored and (co)edited numerous books, of which, the most important ones are Looking through Images. A Phenomenology of Visual Media (Columbia University Press, 2021), Dynamis of the Image. Moving Images in a Global World (De Gruyter, 2020), Partages de la perspective (Fayard, 2020), Resistance of the Sensible World: An Introduction to Merleau-Ponty (Fordham University Press, 2017). He is the recipient of the Latsis Prize 2016 and the Aby Warburg Prize 2019 and currently serves as President of the German Society of Aesthetics. In 2021, Professor Alloa gave an online cycle of lectures titled Orbis Pictus. A Media Phenomenology in an Image World at Vilnius University. This year, I had the pleasure to hold an online conversation with Professor Alloa as he kindly agreed to discuss the topic of images and his project of symptomatology. The interview encompassed questions about the relation of an image with the image theories, the differences between the symptomatological approach to images and the visual semiotics, Derrida’s contribution to the problem of mediality, and the role of images in the philosophy today. This interview was taken on the 20th of June, 2023